Analisis Keberlakuan Efek Kurva J pada Hubungan Bilateral Indonesia-ASEAN 5: 2010.1-2021.4 - Muntaz Ndaru Apsari; Fransiscus Xaverius Sugiyanto (Diponegoro Journal of Economics, 2023)
This study was conducted to examine the J-curve effect in the bilateral relationship between Indonesia and the ASEAN-5 countries, as well as to understand how the AFTA and MEA programs related to economic openness influence the formation of the J-curve in this bilateral relationship. The variables used in this research are bilateral net exports between Indonesia and the ASEAN-5, bilateral real exchange rates, and the degree of bilateral economic openness between Indonesia and the ASEAN-5. Based on the results of the regression analysis, it indicates that the bilateral relationship between Indonesia and the ASEAN-5 during the period from Q1 2010 to Q4 2021 does not confirm the existence of the J-curve effect, and the degree of economic openness significantly influences bilateral net exports in the Indonesia-Thailand and Indonesia-Malaysia relationships. The elasticity of the real exchange rate and the degree of economic openness with respect to net exports is related to the existence and formation of the J-curve.